Effects of different processing methods on the lipid composition of hazelnut oil: A lipidomics analysis - Jiayang Sun; Xiaonuo Feng; Chunmao Lyu; Shuang Zhou; Zixuan Liu (Food Science and Human Wellness)
Although hazelnut oil is rich in nutrients, its quality is greatly affected by how it is processed. However, no studies to date have comprehensively analyzed the lipid composition of hazelnut oil using different processing methods. Here, we conducted a lipidomics analysis using UPLC-QTOF-MS to characterize the lipid composition of cold-pressed hazelnut oil (CPO), ultrasonic-assisted hexane hazelnut oil (UHO) and enzyme-assisted aqueous hazelnut oil (EAO). A total of 10 subclasses of 98 lipids were identified, including 35 glycerolipids (GLs), 56 glycerophospholipids (GPs) and 7 sphingolipids (SPs). The total lipid and GL content were the highest in CPO, GP content was the highest in UHO and the ceramide content in SPs was most abundant in EAO. Multivariate statistical analysis showed that the lipid profiles of hazelnut oil prepared with different processing methods varied. Twelve significantly different lipids (TAG 54:3, TAG 52:2, TAG 54:4, TAG 54:2, TAG 52:3, TAG 54:5, DAG 36:2, DAG 36:4, DAG 36:3, PC 36:2, PA 36:2 and PE 36:3) were identified, and these lipids could potentially be used as biomarkers to distinguish between hazelnut oil subjected to different processing methods. Our results provide useful information for hazelnut oil applications and new insight into the effects of edible oil processing.